(untitled) (Plant Tissue Culture and Biotechnology, 2018)
Induced mutations are important for creating novel variabilities in marigold for different purposes. Distinct putative mutants of marigold var. Pusa Narangi Gainda generated through gamma irradiation (in vivo and in vitro), were studied for variability and correlation in M2 generation for 11 traits. The maximum heritability (h2) was noted for days to flower harvest (0.9982%). The highest positive phenotypic correlation (0.637) was noted for number of flowers per plant to the days to first flower harvest. The most positive genotypic correlation (0.915) was found for seed yield (g) to the number of flowers per plant. Furthermore, the putative mutants in M2 were assessed for their diversity using ISSR markers and the amplified DNA fragments were compared with their respective parent genotype maintained (in vivo and in vitro). Single marker regression analysis indicated that the ISSR 811 and ISSR 817 were highly efficient markers for mutant identification in marigold. On the basis of dendrogram, putative mutant No. 3 (pm3) showed the highest dissimilarity with the parent (0.58). The mutants, pm5 and pm6 were found to be similar to each other (0.65), though they were quite distinct from the parent genotype morphologically. These selected mutants were multiplied up to six generations to attain the desired level of homozygosity for their large scale field evaluation. Plant Tissue Cult. & Biotech. 28(2): 223-236, 2018 (December)